The fate of the original rejected articles. Analysis in a public health journal in Latin America - Arroyo-Hernández, Hugo (2023)
Introduction: Research published in scientific journals allows generating evidence for decision making. However, the destination of the research received in a scientific journal is not always its publication. Objective: To determine the destination of the original articles that were rejected in the Peruvian Journal of Experimental Medicine and Public Health (RPMESP) during 2014 and 2015 and the factors associated with their publication. Materials and methods: During June and July 2019, a Google Scholar search was carried out for the original articles that were rejected in the RPMESP, the gender, origin and academic degree of the corresponding author were evaluated as independent variables, in addition to whether he rejected was made by the editorial committee or after being reviewed by peers. To determine the associated factors, bivariate (RR) and multivariate (RRa) relative risks were calculated with 95% confidence intervals (95% CI) using a simple and multiple Poisson regression model. Results: Of 285 original articles rejected, 45.6% were destined for publication in other scientific journals, of which 61.5% were foreign journals, the corresponding authors with foreign affiliation (RRa 1.34, CI 95%: 1.02-1.77) and undergraduate students (RRa 1.56, 95% CI: 1.12-2.17) increased the probability of publication, but it decreased if the rejection was after peer review (RRa 0.71, 95% CI: 0.52-0.97). Conclusions: Less than half of the original articles that were rejected were destined for publication in another scientific journal. The authors must analyze the reasons for the rejection and continue with the publication process.